ANTECEDENTS AND CONSEQUENCES OF MOTIVATION, SELF-ESTEEM, ACADEMIC CULTURE, SOCIAL INTELLIGENCE, AND LEARNING BEHAVIOR TO THE LEVEL OF UNDERSTANDING OF ACCOUNTING - Yuliarini, Sarah; Gultom, Desi Monarista (Review of Management and Entrepreneurship, 2020)
This study aims to explain the factors that can influence the students at the University of Wijaya Kusuma Surabaya in understanding accounting as a form of knowledge. Determination of samples uses the purposive sampling method and resulted in 60 respondents. This study collected samples of seventh semester accounting students who are submitting their undergraduate final assignments, and the sample have fulfilled the required accounting courses. Not all of the variables analyzed influence the level of understanding of accounting. The variable of Social Intelligence, the variable of Learning Behavior, and the variable of Academic Culture are proven to have influence on students’ understanding of accounting. The variable of Motivation and Self-Esteem have no influence on the students’ level of understanding on accounting.